Modern baby breastfeeding trends - A. Kachurenko; L. Levadna; A. Horobets; Yu. Proshchenko; Ya. Kalinichenko (Zaslavsky O.Yu., 2023)
Breastfeeding is a critical aspect of infant care that provides numerous benefits for both infants and mothers. The socio-cultural changes of the 21st century require optimisation of this practice and research into the physiological stages of milk secretion, including the hormonal regulation of lactation and factors that influence breast secretion, which is crucial for supporting breastfeeding and improving the overall well-being of infants and mothers. The purpose of the work was to investigate current views on breastfeeding support through a comprehensive review of the existing literature, with a particular focus on studies on the physiological stages of milk secretion during pregnancy and breastfeeding. We used bibliographic, analytical and regulatory search methods. The review contributes to the deepening of knowledge and understanding of breastfeeding, emphasising its importance for newborn care and maternal well-being. The material covers a wide range of factors that influence lactation as a physiological process and breastfeeding as a social practice. The findings highlight the physiological basis of the lactation process: the key role of prolactin and oxytocin in initiating and maintaining milk secretion, internal (hormonal imbalances, breast anatomy and surgery), and external factors such as the mother's somatic condition, including gestational diabetes and polycystic ovary syndrome. The positive aspects of breastfeeding for both the child and the mother are analysed. The various positive effects of this practice on the child are considered, including the most favourable balance of nutrients in the mother's milk, the formation of passive immunity and the maintenance of a healthy intestinal microbiota. Particular attention is paid to the changing views on infant feeding in light of social and economic changes in the early 21st century, including the growing role of artificial formula and the challenges of natural feeding in the workplace. Practical implications: it provides a basis for developing evidence-based interventions to improve the breastfeeding experience and well-being of both infants and mothers while informing healthcare professionals, policymakers, and support groups.